A safe production process of alkylene oxide from alkylene carbonates - Gianmarco Polotti; Massimo Barbieri; Davide Moscatelli (Invention Disclosure)
Alkylene oxides of low molecular weight, ethylene, and propylene oxides, have a widespread use in industry. They are used to produce other chemicals and products such as solvents, surfactants, antifreeze, adhesives, polyurethane foams, and pharmaceuticals. They are also used as fumigants in agricultural products and as sterilant for medical equipment and supplies. Unfortunately, it is worth noting that alkylene oxides also possess several physical and health hazards that merit special attention. They are flammable,explosive and their storage and transportation warrant stringent safety rules. The obvious solution to reduce the risk is to generate them from intermediate safety materials only when and only where they are necessary. The literature suggests that correspondent carbonates are very stable precursors. The scope of our study is that of identifying the optimal conditions to generate ethylene and propylene oxide in the moment just before their reaction and uses. The patent deals with some equipment and process conditions that guarantee a fast and reliable dissociation of carbonates in their correspondent oxides. The natural output of the patent is a unit able to provide the dangerous material in situ, under controlled conditions . As a results, all the risks related to transportation and storage are eliminated.